Why wonder bread lost no dough: Materiality, settlements and the FTC's ad sustantiation program - Richard S. Higgins; Fred S. McChesney (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
Previous studies (e.g., by Sam Peltzman) reveal powerful share-value effects of Federal Trade Commission (FTC) actions against firms for allegedly false advertising. Curi- ously, however, when the FTC announces an investigation but simultaneous settlement of the case with the advertiser, no adverse impact results, an empirical finding thus far un- explained. This article uses a recent FTC action, in which the accused advertiser suffered no adverse equity impact, to explain that result. The article focuses on the empirical is- sue of materiality. Many advertising messages challenged by the FTC are not material to consumers. If not - and especially when, as in the case discussed here, the advertiser had much earlier discontinued the advertising challenged - the advertiser predictably would not suffer. Econometric evidence strongly indicates that the messages the FTC chal- lenged were immaterial to consumers.
Keywords: 330